Antibacterial Activity of Some 4-Pyridinone Derivatives Synthesized from 4-Pyrones - ATALAN, E.; BIYIK, HALIL; BATTAL, H.; OZDEMIR, K. (Asian Journal of Chemistry, 2010)
Antibacterial activity of total 11 newly synthesized compounds of 4-pyrone and 4-pyridinone derivatives were determined against standard bacterial test microorganisms by the tube dilution technique. Most of the compounds, except compound 11, exhibited antimicrobial activity towards the gram-negative bacterium Escherichia coli, while other compounds inhibited either 1 or 2 or 3 the growth of test microorganisms. Antibacterial activities of the compounds were exhibited strong activity and some were moderate activity while none of compounds did not inhibit the growth of S. aureus, S. pyogenes, E. facealis and B. subtilis.